Motivating Alzheimer's Disease and Related Dementia Risk Reduction Behaviors in Older Adults: Motivational Cessation Message Development Findings. (20th December 2022) - Johnson, Adrienne L.; Gleason, Carey E.; Cook, Jessica; Mahoney, Jane; Piper, Megan E.
Abstract: Background: Smoking, a modifiable risk factor for dementia, accounts for at least 14% of current Alzheimer's disease cases. Older smokers are more likely to remain abstinent than younger adults when they use evidence‐based smoking treatment (EBST), thereby reducing their dementia risk. Unfortunately, older smokers are half as likely to try to quit than younger adults. Therefore, motivating older adults to quit using EBST is a vital public health priority. Method: 24 current smokers [ M = 14.3 ( SD = 9.5) cigarettes/day] with no dementia/MCI history, ages 50‐75 years, 83% White, 12.5% African American, 4% Mixed race, and 79% cisgender female completed a 2‐hour semi‐structured interview and survey via telephone that was analyzed using rapid content analysis. Result: The most commonly reported health‐related concern was dementia/cognitive loss/loss of functioning, followed by cancer, heart attack/CVD, COPD/emphysema, pain/arthritis, falling, and death. Most participants believed they were at risk of their feared health‐consequence, and that quitting would help. Although all participants had seen previous advertisements for smoking cessation, the majority did not feel motivated to quit by these advertisements. Half of participants were unaware of any link between smoking and dementia, and only a quarter of participants remembered specifics about this link. The vast majority found a message about smoking raising dementia risk and quitting as a means to decrease that risk as motivating for cessation, with over half of participants stating this type of message would be more motivating than previous cessation advertisements. There were varied preferences for exact message content, but two broad categories arose: hope/change of quitting‐based messages and fear/risk of smoking‐based messages. Most participants were aware of smoking cessation pharmacotherapies from personal/relatives past use, but previous negative side effects, cessation failure, and cost were barriers to future use. Nevertheless, the majority of participants stated willingness to use some cessation pharmacotherapy. Many had not considered cessation counseling and were unaware how to access it; half were willing to use cessation counseling. Conclusion: Hopeful/change‐ and fear‐based messages around smoking and dementia risk could motivate cessation for older smokers. Although dementia is an important health consequence of smoking, older smokers are unaware of this modifiable risk factor.